Impacts of gibberellin (GA3) on sensorial quality and storability of table grape (Vitis vinifera L.) - Denis RUSJAN (Acta Agriculturae Slovenica)
The eventual impacts of the gibberellin (GA3) application on grapevine (Vitis vinifera L.) varieties 'Cardinal' and 'Michele Palieri', on grape quality and their storage potential were studied. The grape quality was determined as individual and total carbohydrates and organic acids, but also the external skin colouration was measured. The measurement of polyphenol oxidases (PPO) activity was contributed to clearly understand storage potential. During the grape maturation the statistical differences in grape quality were observed according to the treatments. The treatments with GA3 showed similar and related impacts on grape quality at both varieties only at harvest, where the statistically highest total sugar concentration (223-226 g kg-1) was determined at 50 ppm, followed by 20 ppm (216-223 g kg-1) and the lowest 201-220 g kg-1 at control. The organic acid concentrations in the grape of both varieties did not show any similar correlation according to treatments. The PPO activities were slightly higher at mature grape of 'Cardinal' (2.5-3.0 ?A min-1g-1) compared to 'Michele Palieri' (1.0-1.2 ?A min-1g-1), and the activities at both varieties during storage decreased. At harvest the CIRG indices of 'Cardinal' (5.5-6.1) and of 'Michele Palieri' (6.6-6.9) did not statistically differ among treatments as at the end of storage, where the highest indices were calculated at treatment 50 ppm at both varieties. The grape quality of table grape responded differently to GA3 applications, especially the different impacts were observed according to varieties.